WEB-BASED ACADEMIC INFORMATION SYSTEM OF YAPI SUNNI TEGALGONDO ISLAMIC BOARDING SCHOOL USING WATERFALL METHOD TO MANAGE STUDENTS ACADEMIC DATA - Sang Aji Indutoro; Endah Sudarmilah (Informatika, Universitas Jenderal Soedirman, 2022)
Yapi Sunni Islamic Boarding School is one of the Islamic da'wah and education foundations located in Tegalgondo, Wonosari, Klaten. Yapi is active in the management of religious education with the vision of creating a generation of Muslims who are expected to be the successors of future generations who are tough and knowledgeable. The students' academic data management system to report generation, Yapi Islamic Boarding School uses a combination of manual data recording with paper media, archives, and Microsoft Office which in its application often problems arise when collecting data manually and the possibility of being damaged, lost or exposed to a virus attack is quite high. This study aims to design a web-based Islamic boarding school academic information system that can provide access for aliyah level student academic data managers and provide access for student parents to monitor their child's development. The system will be designed using the PHP programming language, MySQL as database management, and the CodeIgniter framework. The system development method used in this research is the waterfall method. The result of this research is a web-based Yapi Sunni Islamic boarding school information system. Based on the results of blackbox testing, this system can run well and the results of UAT testing carried out by users, obtained an average percentage of 93%, it can be concluded that the system is in accordance with the needs and can be accepted by user.